Four Inducible Promoters for Controlled Gene Expression in the Oleaginous Yeast Rhodotorula toruloides - Johns, Alexander M. B.; Love, John; Aves, Stephen J. (Frontiers in Microbiology, 2016)
Rhodotorula (Rhodosporidium) toruloides is an oleaginous yeast with great biotechnological potential, capable of accumulating lipid up to 70 % of its dry biomass, and of carotenoid biosynthesis. However, few molecular genetic tools are available for manipulation of this basidiomycete yeast and its high genomic GC content can make routine cloning difficult. We have developed plasmid vectors for transformation of R. toruloides which include elements for Saccharomyces cerevisiae in-yeast assembly; this method is robust to the assembly of GC-rich DNA and of large plasmids. Using such vectors we screened for controllable promoters, and identified inducible promoters from the genes NAR1, ICL1, CTR3 and MET16. These four promoters have independent induction/repression conditions and exhibit different levels and rates of induction in R. toruloides, making them appropriate for controllable transgene expression in different experimental situations. Nested deletions were used to identify regulatory regions in the four promoters, and to delimit the minimal inducible promoters, which are as small as 200 bp for the NAR1 promoter. The NAR1 promoter shows very tight regulation under repressed conditions as determined both by an EGFP reporter gene and by conditional rescue of a leu2 mutant. These new tools facilitate molecular genetic manipulation and controllable gene expression in R. toruloides.